(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In recent years, the area of sketch-based virtual garments generation has attracted more and more attention. In this paper, we propose a new method to develop 3D virtual garments by applying mesh deformation technology for the sketch-based approach. Compared to the traditional methods, the 3D garments, generated by our method, can be obtained easily and directly. The technology of mesh deformation in our paper involves two algorithms: Laplacian mesh editing/optimization, and mean-value geometry encoding/decoding. Given the modified positions for a set of anchor vertices, the mean-value encoding and decoding are used to transform the positions for the rest of the mesh vertices. Laplacian mesh editing and optimization are capable of improving the quality of the triangulation while preserving the shape properties of the original models. The resulting 3D garment validates the effectiveness of the proposed method.